Labour markets, worker protection, and lifelong learning in a global economy : experiences and perspectives of Latin America - Weller, Jürgen [et al.] (ECLAC [Santiago]CL, 2008)
Describes the situation and recent labour market trends in the region and looks at the characteristics of labour market institutions. Focuses on the change introduced in recent years in the three pillars of labour market institutionality; labour market regulation; unemployment protection and active labour market policies. Discusses flexicurity and analyzes the hurdles that Latin America and Caribbean countries will need to overcome in order to change their institutions, bearing in mind the basic tenets of flexicurity. Puts forward proposals for reforming the three areas of labour institutionality.